Analisis Manajemen Risiko pada UMKM Depo Air Minum BIRU Ciwastra Kota Bandung - Muhammad Shoffan Anbiya; Almaira Sarah Junjunan; Nisa Febrianti; Sarah Mutia Azahra; Alfiana Alfiana (Indo Publishing, 2026)
Drinking Drinking water refill depots are one of the MSME sectors that play an important role in meeting the drinking water needs of urban communities. Depo Air Minum BIRU Ciwastra is an MSME engaged in drinking water refill services located in Bandung City. This study aims to analyze the risk management practices implemented at Depo Air Minum BIRU Ciwastra using a descriptive qualitative approach based on the ISO 31000:2018 framework. Data were collected through field observations, interviews with the business owner, and documentation review. The results indicate that there are six main categories of risk, namely operational, financial, human resources, market, marketing, and legal risks, with a total of 30 identified risk events. The highest risk levels were found in operational, market, and financial aspects, which directly affect water quality, service performance, and cash flow stability. Risk mitigation strategies include routine machine maintenance, separation of business and personal finances, improvement of human resource competencies, optimization of digital marketing, and periodic water quality testing. The systematic implementation of risk management is expected to enhance business resilience, service quality, and the long-term sustainability of drinking water refill MSMEs amid increasingly intense competition.